AB0488 Capillaroscopy findings in childhood-onset systemic lupus erythematosus, a dutch experience of 20 children and adolescents. (15th June 2017) - Schonenberg-Meinema, D; Berg, M vd; Nassar-Sheikh-Rashid, A; Bree, G de; Hak, L; Onna, M van; Melsens, K; Cutolo, M; Kuijpers, T; Smith, V
Abstract : Background: Capillaroscopy findings can be qualitatively described as: normal, microangiopathy (non-specific abnormalities) or scleroderma pattern (1). Capillary abnormalities, described in varying prevalence in patients with systemic lupus erythematosus (SLE), are mainly described as microangiopathy (2–4) Objectives: To describe capillary characteristics in a cross-sectional cohort of patients with childhood-onset SLE (cSLE) by quantitative and qualitative assessment Methods: Nailfold videocapillaroscopy (NVC) was performed in cSLE-patients (onset <18 years) with a x200 magnification lens (Optilia). The following capillaroscopic characteristics were evaluated per millimeter: density (compared to mean density known for age, sex and ethnicity) (5), number of abnormal shapes (as defined by the EULAR study group on microcirculation in Rheumatic Diseases (6)), giant capillaries (defined as apical diameter >50 mcm), maximum apical diameter (dilatations defined as apical diameter 20–50mcm) and microbleedings (large hemorrhages and small multiple point-shaped hemorrhages surrounding the capillary loop [image]) Results: 4063 capillaries from 20 patients with cSLE, were analyzed. All patients showed capillary abnormalities, 15% (n=3) showed a scleroderma-pattern. A lower mean density (mean 6.7, range 1.9–9.5) was seen in 55% (n=11), multiple (>8 per patient) abnormal shapes in 60% (n=12), apical dilatations in 90% (n=18). Total count of large/small point shaped hemorrhages was 109/855, with a mean of 0.2/1.6 per analyzed image/per patient. These were detected in 85/85% of patients (n=17) Conclusions: In this pilot (n=20) of cSLE patients, all showed capillary abnormalities. The most striking finding was the point-shaped bleeding surrounding the capillary, observed in 85% (n=17) of our patients. Prospective longitudinal cohort studies in children through the EULAR study group on microcirculation in Rheumatic diseases will elucidate whether specific findings can be found in child rheumatic diseases References: Cutolo M. Atlas of capillaroscopy in rheumatic diseases. Milan: Elsevier; 2010. Ingegnoli F. Capillaroscopy abnormalities in relation to disease activity in juvenile systemic lupus erythematosus. Microvascular research. 2013;87:92–4. Dolezalova P, Young SP, Bacon PA, Southwood TR. Nailfold capillary microscopy in healthy children and in childhood rheumatic diseases: a prospective single blind observational study. Ann Rheum Dis. 2003;62(5):444–9. Shenavandeh S, Habibi S. Nailfold capillaroscopic changes in patients with systemic lupus erythematosus: correlations with disease activity, skin manifestation and nephritis. Lupus 2017:961203316686702. Terreri MT, Andrade LE, Puccinelli ML, Hilario MO, Goldenberg J. Nail fold capillaroscopy: normal findings in children and adolescents. Seminars in arthritis and rheumatism. 1999;29(1):36–42. Smith V, Beeckman S, Herrick AL, Decuman S, Deschepper E, De Keyser F, et al. An EULAR study group pilot study on reliability of simple capillaroscopic definitions to describe capillary morphology in rheumatic diseases. Rheumatology (Oxford). 2016;55(5):883–90. Disclosure of Interest: None declared